The innovation potential of the enterprise in the context of the economy and the business model - Krawczyk‑Sokolowska, Izabela (Springer Nature, 2020)
The objective of the paper is to identify the factors of innovative potential in Pol‑ish enterprises that are key from a perspective of enterprise’s innovativeness (micro scale) and their impact on the economy (macro scale). Based on original methodol‑ ogy of research, 36 factors of innovative potential of Polish enterprises were iden‑ ti ed. Next, they were aggregated according to micro criteria, taking the order of organization proposed by H.J. Leavitt as well as macro criteria, which included the analysis of the factors of innovative potential of enterprises in a context of inno‑vation subsystems of the economy. The analysis also takes into account business models in micro and macro scale. The conclusions formulated are a qualitative diag‑nosis of the activities of Polish enterprises in terms of innovation development and implementation, and also the economy was assessed regarding innovative potential in a macro scale.